In situ coherent X‐ray diffraction imaging of radiation‐induced mass loss in metal–polymer composite spheres. (5th June 2018) - Skjønsfjell, Eirik Torbjørn Bakken; Chushkin, Yuriy; Zontone, Federico; Breiby, Dag Werner
Abstract : Coherent X‐ray imaging of radiation damage to metal‐coated polymer microspheres is reported. Abstract : A major limitation to the use of coherent X‐ray diffraction imaging (CXDI) for imaging soft materials like polymers and biological tissue is that the radiation can cause extensive damage to the sample under investigation. In this study, CXDI has been used to monitor radiation‐induced structural changes in metal‐coated poly(methyl methacrylate) microspheres. Using a coherent undulator X‐ray beam with 8.10 keV photon energy, 14 tomograms at a resolution of ∼30 nm were measured consecutively, which resulted in an accumulated dose of 30 GGy. The three‐dimensional images confirmed that the polymer core was strongly affected by the absorbed dose, giving pronounced mass loss. Specifically, as the metal–polymer composite was exposed to the X‐ray beam, a bubble‐like region of reduced density grew within the composite, almost filling the entire volume within the thin metallic shell in the last tomogram. The bubble seemed to have its initiation point at a hole in the metal coating, emphasizing that the free polymer surface plays an important role in the degradation process. The irradiation of an uncoated polystyrene microsphere gave further evidence for mass loss at the free surface as the radius decreased with increased dose. The CXDI study was complemented by X‐ray photon correlation spectroscopy, which proved efficient in establishing exposure dose limits. Our results demonstrate that radiation‐induced structural changes at the tens of nanometer scale in soft materials can be followed as a function of dose, which is important for the further development of soft‐matter technology.